Designing and developing secure Azure solutions - Howard, Michael; Gantenbein, Heinrich; Curzi, Simone (Pearson Education, 2023)
As business-critical applications and workloads move to the Microsoft Azure cloud, they must stand up against dangerous new threats. That means you must build robust security into your designs, use proven best practices across the entire development lifecycle, and combine multiple Azure services to optimize security. Now, a team of leading Azure security experts shows how to do just that. Drawing on extensive experience securing Azure workloads, the authors present a practical tutorial for addressing immediate security challenges, and a definitive design reference to rely on for years. Learn how to make the most of the platform by integrating multiple Azure security technologies at the application and network layers taking you from design and development to testing, deployment, governance, and compliance.